Multi-objective energy efficient resource allocation for WPCN - Sharma, S.; Yoon, W. (International Journal of Engineering Research and Technology, 2018)
In this paper, we propose an energy-efficient resource allocation scheme for a wireless powered communication network (WPCN). A multiple-objective optimization problem (MOOP) is formulated for the EE maximization for every user. We exploit fractional programming approach to convert the non-convex problem into a standard convex optimization problem. This allows us to derive an efficient iterative algorithm for Pareto optimal. Simulation results prove our theoretic findings and show that distributed massive multi input multi output (MIMO) performs better and higher as compared to that of centralized massive MIMO.
Keywords: Energy efficiency; Generalized fractional programming; Pareto optimal; Wireless powered communication network